PEMBENTUKAN DAN PENGAWASAN PRODUK HUKUM DAERAH - Sukriono, Didik (JURNAL KONSTITUSI, 2011)
Area autonomy is often translated by local government of identical at the increasing of native earnings of region (PAD) as much as possible. By law (Perda) represent looked into instrument " legal" to collect fund of society. Only its problems thousands of perda which have been published by local government since 1999 (autonomous era of region) generally represent perda "having problem", and low subvention of him awareness of local government report perda which have been released to central government. Effort overcome perda having problem, MPR at annual conference of MPR RI on 2001, recommending to appellate court to test material (judicial review) to all perda which oppose against law and regulation of super ordinate. In the 2006, DPR submit "memorandum" refusing and asking for president repeal various perda of sub-province / municipality regarding "anti immoral". UU no.32 on 2004 (section 145) expressed by perda, which oppose against public interest and / or law and regulation of super ordinate can be canceled by government pass regulation of president. Thereby controlling to Perda has problem, Indonesia embrace examination model "executive review" and " judicial review ". This matter can be seen from rule of alteration of the constitution (UUD) 1945 section 24 A sentence (1), specifying authoritative appellate court judge at level of cassation, testing law and regulation under code to law, and have other authority which given by code and section 11 sentence (2) letter of b UU no.4 on 2004 about judicial power and section 31 UU no.5 on 2004 about appellate court and of UU no.32 on 2004 about local government.Â